Performance assessment of state-of-the-art and novel methods for remote compliance monitoring of sulfur emissions from shipping - J. Beecken; J. Beecken; A. Weigelt; S. Griesel; J. Mellqvist; A. V. Conde Jacobo; D. van Dinther; J. Duyzer; J. Knudsen; B. Knudsen; L. Ntziachristos (Atmospheric Measurement Techniques, 2023)
The fuel sulfur content (FSC) of ocean-going and inland vessels was measured simultaneously by eight different state-of-the-art and novel monitoring systems during a 6-week campaign at the Elbe River, at a distance of about 10 km to the port of Hamburg, Germany. Both stationary and airborne systems on unoccupied aerial vehicles (UAVs) were operated by four participating partners in a side-by-side measurement setup to measure the emission factors of the same emission sources. A novel laser spectrometer, with significantly better-precision specifications as compared with the other instruments, was used for the first time for emission monitoring regarding the International Convention for the Prevention of Pollution from Ships (MARPOL) Annex VI regulations.